Capital Structure, Firm Size and Market Value of Share Price - Empirical Evidence from Transportation & Logistics Sector in Bursa Malaysia - Fatin Aryssa Yasmeen Zamani; Manisa Tharumalingam; Abdul Razak Bin Abdul Hadi (EQUITY, 2026)
The main objective of this study to examine the impact of capital structure and firm size on firm value in the transportation and logistics sector in Bursa Malaysia. This study primarily puts its focus on investigating how the market value of share price of 25 logistics companies listed in the main board would respond to dynamic changes in capital structure and firm size (as measured by total assets).  Methodologically, we deploy static panel data regression models to estimate the theoretical model within the context of capital structure and asset utilization theories.  Our observation period spans over ten years starting from 2015 through 2024 involving yearly time series data.  The statistical results from both Pooled Ordinary Least Squares (OLS) and Fixed Effect models show that firm size and sales exert significant influence on firm value but this does not apply to capital structure.  Our findings suggest that total assets and sales are the primary indicators of firm’s financial health that drive up the market value of share price (increased valuation). It is therefore evidential to us that the Modigliani-Miller and Signaling theories provide meaningful explanations on the relationship between firm size, sales and firm value in the transportation and logistics sector in Bursa Malaysia.